Localized Castleman’s Disease in the Breast in a Young Woman (2016)
Castleman’s disease (CD) is a rare lymphoproliferative disorder of unknown etiology. It typically occurs in adulthood but it may also develop in childhood. Clinically, this disease may be classified as localized (unicentric) or systemic (multicentric). Six cases of breast CD have been described in the literature, and all have been reported in adults. Herein we describe the case of a 15-year-old female who presented with a slow-growing tumor in the right breast. The tumor was excised and histopathological examination demonstrated hyaline vascular variant CD. After two years of follow-up, the patient was asymptomatic without evidence of cervical or axillary lymphadenopathy.